Assessment of Psychological Birth Trauma and Related Factors in Primiparous Women in Hospitals of Mashhad University of Medical Sciences - Golnaz Sadat Ahmadinejad; Seyedeh Fatemeh Nosrati Hadiabad; Seyyed Majid Sadrzadeh; Fatemeh Zahra Karimi (Hamadan University of Medical Sciences, 2024)
Background and Objective: Psychological childbirth trauma occurs as a result of physical or psychological traumatic experiences during labor and delivery, and the mother shows a response in the form of fear, despair, loss of control, helplessness, and panic. It can also cause complications in the postpartum period, such as disrupting the relationship between mother and child and communication with her husband in the future. The present study was conducted to investigate the level of psychological childbirth trauma and the related factors in primiparous women in the teaching hospitals of Mashhad University of Medical Sciences in 2022. Materials and Methods: This cross-sectional study was conducted on 484 primiparous women in the Midwifery Department of educational hospitals of Mashhad University of Medical Sciences in 2022. The data collection tool included a demographic profile form and the Psychological Childbirth Trauma Questionnaire. Data analysis was done using SPSS version 21 software, and descriptive statistical tests (mean, standard deviation, number, and percentage) and regression were used. A p-value of less than 0.05 was considered significant. Results: The average score for the total psychological childbirth trauma was obtained at 45.52 ± 18.51, and the average score for anxiety and hotness of childbirth, psychological manifestations, helplessness, collapse, sense of death, and physical manifestations was 16.31 ± 7.44, 11.20 ± 4.97, 9.73 ± 4.80, 3.82 ± 1.67, 4.46 ± 2.06, and 4.46 ± 2.06, respectively. There was a significant relationship between psychological childbirth trauma and family income level (P=0.030), unwanted pregnancy (P<0.001), primiparous birth (P<0.001), and newborn APCAR score (P=0.001). Conclusion: Considering the incidence of postpartum psychological trauma and the existence of a relationship between first birth, family income level, unwanted pregnancy, and the APCAR score of the newborn, healthcare workers should identify women at risk of postpartum psychological trauma as soon as possible and prevent the occurrence of resulting injuries by performing preventive measures and early interventions.